Antibiotics and antibiotic resistance genes in agricultural soils: A systematic analysis. Issue 7 (3rd April 2023) - Wu, Jie; Wang, Jinyang; Li, Zhutao; Guo, Shumin; Li, Kejie; Xu, Pinshang; Ok, Yong Sik; Jones, Davey L.; Zou, Jianwen
Abstract: Misuse and overuse of antibiotics have contributed to the rise of antimicrobial resistance as one of the top public health threats. Antibiotics and antibiotic resistance genes (ARGs) are prevalent in agricultural soils due to the widespread application of livestock and organic wastes. However, information about the occurrence, distribution, and risk of antibiotics and ARGs in agricultural soils is lacking for many scenarios. In this study, based on 2225 observations from 135 independent studies, we summarized the concentration or abundance of antibiotics or ARGs under different fertilizer sources and land-use patterns, analyzed the contributions of key environmental factors to the occurrence of antibiotics and ARGs in agricultural soils, and highlighted the potential ecological risk of typical antibiotics and the relationship between ARGs and mobile genetic elements (MGEs). Our results showed that cattle manure, chicken manure, swine manure, and sewage sludge were the primary pollution sources of antibiotics and ARGs in agricultural soils, and sulfonamides, tetracyclines, fluoroquinolones, and their corresponding ARGs were the main pollution types. Land-use type, soil, and climatic factors affected antibiotics concentration and ARG abundances. MGEs play a vital role in promoting the dissemination of ARGs, especially the sul 1 gene is closely related to intI 1. In conclusion, our findings and future research exploring these topics will contribute to better management of antibiotic and ARG contamination in agricultural soils and their risk to human health. Graphical abstract: UF0001